Sustainable Innovation in Community Service through Digital Transformation and Community Empowerment to Achieve an Adaptive and Resilient Social Ecosystem - Sutrisno; Abu Muna Almaududi Ausat; Suherlan (Tirakat: Jurnal Terobosan Peduli Masyarakat, 2026)
This study aims to analyze sustainable innovation in community service through the integration of digital transformation and community empowerment as an effort to achieve an adaptive and resilient social ecosystem. This research employs a qualitative approach using a literature review method focused on collecting and synthesizing findings from previous studies. Specifically, this study seeks to enrich references related to community service by emphasizing the importance of integrating technological and social aspects. Data were obtained from Google Scholar and various credible websites within the period of 2000–2026. From an initial search of 50 articles, a rigorous selection process based on relevance, quality, and scientific contribution resulted in 34 articles for further analysis using qualitative descriptive techniques. The findings indicate that digital transformation enhances efficiency, information access, and the reach of community service programs. However, without community empowerment, program sustainability remains limited. Conversely, community empowerment without technological support tends to be less effective in addressing dynamic changes. Therefore, integrating both aspects is crucial for creating sustainable innovation.